Kajian sosial ekonomi pada petani garam di wilayah Madura - Kustiawati Ningsih; Nur Laila (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
As one of the islands in Indonesia , Madura is one of the salt-producing centers in Indonesia , thus earning the nickname as the Salt Island. Therefore, almost 80% of the population in Madura have a livelihood as salt farmers and including salt farmers in Bunder Village, Pademawu District, Pamekasan Regency. However, the weak adoption power of Madura salt farmers in Bunder Village, Pademawu District, Pamekasan Regency to the new technology, namely geomembrane, has a very significant socio-economic impact on salt farmers. So the purpose of this study was to examine the socio-economic conditions of Madura salt farmers in Bunder Village, Pademawu District, Pamekasan Regency. Data were collected through primary data (observations and interviews) and secondary data. The data obtained from the results of the study were processed using qualitative analysis (income analysis) and quantitative analysis (range score analysis of BPS welfare indicators in 2015) to ensure the socio-economic conditions of Madura salt farmers in Bunder Village, Pademawu District, Pamekasan Regency. The results showed that (1) The average monthly income of salt farmers was IDR 1,784,416 per hectare per month (2) The average range score of Madura salt farmers based on the BPS welfare indicators in 2020 was in the poor category.